2013
DOI: 10.1007/978-3-642-40480-1_21
|View full text |Cite
|
Sign up to set email alerts
|

User and System Cross-Learning of Gesture Commands on Pen-Based Devices

Abstract: Part 7: Gesture-Based User Interface Design and Interaction IIInternational audienceThis paper presents a new design and evaluation of customizable gesture commands on pen-based devices. Our objective is to help users during the definition of gestures by detecting confusion among gestures. We also help the memorization gestures with the guide of a new type of menu “Customizable Gesture Menus”. These menus are associated with an evolving gesture recognition engine that learns incrementally, starting from few da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…To improve gesture command recognition, the classifier learns incrementally during its use. At the same time that the classifier is learning, so is the user: he has to memorize which gesture is associated with which command [4]. In this cross-learning situation, different cases can happen:…”
Section: The Intuisup Supervisormentioning
confidence: 99%
See 1 more Smart Citation
“…To improve gesture command recognition, the classifier learns incrementally during its use. At the same time that the classifier is learning, so is the user: he has to memorize which gesture is associated with which command [4]. In this cross-learning situation, different cases can happen:…”
Section: The Intuisup Supervisormentioning
confidence: 99%
“…Those gesture commands [1,2] enable users to execute various actions simply by drawing the associated symbols. Previous studies [3,4] have shown that enabling customization is essential to help user memorization of gestures. In order to use such gesture commands, a handwritten gesture recognition system is required.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al presented in their second experiment a way to help the user to learn the gestures [9]. To get help, the user has to activate a widget that shows each command and the related pen-based gesture.…”
Section: Related Workmentioning
confidence: 99%
“…Those gesture commands [1][2] enable users to execute various actions simply by drawing symbols. Previous studies [3] [4] have shown that enabling customization is essential to help user memorization of gestures. To use such gesture commands, a handwritten gesture recognition system is required.…”
Section: Introductionmentioning
confidence: 99%